Reviewing the Potential and Constraints of Modified Technology Options for Faecal Sludge Management in Dar es Salaam, Tanzania - Seleman, Amour; Mbwette, Tolly S.A.; Gabrielsson, Sara; Kimwaga, Richard (Tanzania Journal of Engineering and Technology, 2020)
Cities in the developing world face the challenge of safe management of faecal sludge because of rapid population growth that overwhelms the sanitation infrastructure and services. In developing countries, only 50% of faecal sludge (FS) generated is safely managed the remaining portion is haphazardly disposed of in the environment risking public health and environment. In response to the urgent need for safely managed sanitation services, technological options for containment, desludging and transportation of FS are being modified. This paper reviewed current desludging practices and the potential of modified technological options for addressing FSM at containment, desludging, and transportation in Dar es Salaam unplanned urban settlements. The paper reviewed; water seal squat pan, Urine Diversion Dry Toilet (UDDT), split slabs, pre-installed suction hose, and the container-based sanitation (CBS) for containment stage. Others are the hand tools, sludge digger, the excrevator, rammer, and the eVac for desludging; and small pick-up truck and motorized tricycle and transfer stations for transfer and transportation of FS. Based on technical feasibility, social and environmental context of Dar es Salaam, the reviewed modified technology options have the potential of addressing FSM challenges in unplanned urban settlements in Dar es Salaam. However, institutional arrangement particularly the absence of the modified technologies in the menu of recommended technological options affects their upscaling. Paradoxically, most of the technologies have not been vigorously tried in the field to inform policy choice. Improvement of FSM with the application of modified technological options will require improvement in enabling environment for their operation and continuous modification. The major research gaps have also been identified in this review. Keywords: Containment, Desludging, Faecal Sludge Management, Modified technology options Non-sewered sanitation.